“The Ice is Melting and I Don’t Want Santa to Drown!”: Reflections on Childhood, Climate Action, and Futurity - Hopkins, Lucy (Journal of Childhood Studies, 2023)
This paper’s reading of a specific cultural artifact to emerge from children’s climate activism in contemporary Australia enacts an argument that children themselves can be seen to be redefining childhood and futurity through their climate activism and demonstrates how their placards are evidence of this. It argues that we as critical childhood scholars can follow their lead by uncovering the discourses that underpin their activist slogans. In doing so, we can set about contesting the limiting and disempowering discourses of childhood that would dismiss the very idea of children as political participants in the fight to save the planet.